Preparation and evaluation of some value-added products from hill lemon (Citrus pseudolimon) fruits - SHARMA, P C; SHARMA, S K; LAL KAUSHAL, B B. (The Indian Journal of Agricultural Sciences, 2014)
In an experiment conducted during 1998-99, the suitability of hill lemon (Citrus pseudolimon Tanaka) fruits was evaluated for the preparation of some new products, viz juice concentrate, foam mat dried juice power, carbonated beverage, powdered appetizer and drink. The lemon juice after enzymatic clarification was concentrated to various folds (obrix) using evaporative cacuum concentration. The juice concentration up to 45oB was optomized, as it experienced negligible changes in quality during evaporation. Out of different combinations, the foarm mat drying of juice concentrate (45OB) yielded a juice powder of excellent sensory qualities. Chemically, this powder contained 57.75% acidity (citric acid) and 185.88 mg/100 ml ascorbic acid besides other nutrients. for utilization of juice powder, the standardized recipe for preparing ready-to-serve powdered beverage contained sugar(130 g) lemon essence (4.9 ml), cloud (2.6 ml) and coal tar dye (green 1.5 mg) at a fixed level of 5 gÂ lemon juice powder. The beverage powder on dilution to 1 litre yielded a ready-to-serve drink of acceptable sensory qualities. Addition of appropriate amount of powdered spices 3.75 g ginger, 1.67 g each of mint and cumin, 3.25 g common salt, 1.25 g each of black salt,Â pepper), 125 g sugar, 4.9 ml esilence, 2,6 ml of cloud to 8.75 g of lemon juice powder resulted an an appetizer powder of acceptable’ taste. Further, a lemon beverage containing s% remon juice 0 5% lemon residue extract and 12.5oB total soluble solids was successfully carbonated at 5.28 kg/cm2 CO2 gas ipressure.